Virtual Reality in Samarkand’s Silk Road Museums - Kizi, Toshniyozova Marjona Ikrom (Universitas Andalas, 2024)
This study explores the potential of Virtual Reality (VR) technologies to extend the reach of museum exhibitions in Samarkand, Uzbekistan, by developing virtual exhibits through collaboration between Lublin University of Technology and local museums. The study involved creating a virtual exhibition of 3D-scanned artefacts from three Samarkand museums. An exploratory survey was conducted with museum professionals and Generation Z individuals to assess VR’s complementary role to traditional exhibitions. Findings. The survey revealed broad acceptance of VR as a supplementary tool, with 79% of professionals endorsing it. Generation Z participants showed high engagement, with VR enhancing their interest in traditional visits. VR technologies significantly improve access to Silk Road heritage, providing an immersive, interactive experience that traditional methods cannot offer alone. The findings underscore VR’s potential to attract diverse audiences, particularly tech-savvy younger generations. Integrating VR into museum exhibitions can enhance cultural heritage dissemination, support educational initiatives, and foster a greater global appreciation for Silk Road artifacts. Future research should explore long-term impacts on visitor behavior and museum attendance.